(untitled) (Research, Society and Development, 2023)
This present research aims to analyze in the literature palliative nursing care practices in the quality of life of patients diagnosed with breast cancer. Methodology: it consists of a Literature Review research of the narrative type with a qualitative approach, with an exploratory focus as an inclusion critérios. Thematic relevance was first prioritized, excluding studies that do not explicitly focus on palliative care practices in nursing and that do not specifically address reducing pain and improving emotional support in breast cancer patients. A temporal criterion was established that excludes articles prior to 2018. Result and discussion: To analyze the results, an analytical framework was created that allowed the main information contained in the selected articles to be synthesized, focusing on keywords. Subsequently, a detailed analysis of the 42 selected articles was carried out. However, after this analysis, it was decided to include 18 articles and 3 books on research methodology that were discussed, bringing the authors’ reflection on the topic. Final considerations: Finally, nurses are not limited to helping with symptom management and treatment, they offer emotional support, guidance for home care and play a vital role in promoting patients’ quality of life.